2018
DOI: 10.1182/blood-2018-99-118530
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Follicular Lymphoma Patients Treated with Frontline Bendamustine and Rituximab: Impact of Histologic Grade and Early Progression on Overall Survival

Abstract: Background: Bendamustine and rituximab (BR) is a commonly chosen frontline treatment for grade 1-2 (G 1-2) follicular lymphoma (FL). This regimen resulted in significantly longer progression-free survival (PFS) and less toxicity compared to R-CHOP in the STiL trial [Rummel et al., 2013] and similar results were observed when comparing BR vs. R-CHOP/R-CVP in the confirmatory BRIGHT trial [Flinn et al., 2014, updated ASCO 2017]. Importantly, patients (pts) with grade 3A (G 3A) FL were excluded from these studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…13 Other recent analyses of POD24 after bendamustinebased induction also suggested a decreased risk of POD24 events (9% to 12%), with similarly poor outcomes. 18,19 These findings suggest that early disease-related events after chemomimmunotherapy occur regularly and reproducibly in FL. This work has generated the hypothesis that patients with POD24 are biologically distinct, possessing tumor-and/or host-related factors contributing to chemotherapy resistance, and require novel therapeutic approaches to improve poor outcomes.…”
Section: Validation Studies Of Pod24 Influence On Poor Survivalmentioning
confidence: 76%
See 1 more Smart Citation
“…13 Other recent analyses of POD24 after bendamustinebased induction also suggested a decreased risk of POD24 events (9% to 12%), with similarly poor outcomes. 18,19 These findings suggest that early disease-related events after chemomimmunotherapy occur regularly and reproducibly in FL. This work has generated the hypothesis that patients with POD24 are biologically distinct, possessing tumor-and/or host-related factors contributing to chemotherapy resistance, and require novel therapeutic approaches to improve poor outcomes.…”
Section: Validation Studies Of Pod24 Influence On Poor Survivalmentioning
confidence: 76%
“…28 Recently presented retrospective data suggest that after bendamustine-based therapy, rates of POD24 may be lower (9% to 12%), and among those cases, transformation rates were reported in up to three-quarters of patients. 18,19 However, biopsy to document histologic transformation occurred only in small numbers of patients. As such, these data require validation in larger prospective cohorts.…”
Section: Case 1 Approach: Do You Recommend a Biopsy?mentioning
confidence: 99%
“…The earlier the relapse the greater the potential survival benefit (and, particularly, the lower the potential survival loss) from allogeneic SCT over ASCT (or no SCT). 74 benefit more from anthracycline-based regimens 42,43 (Table 2) although data supporting this idea are indirect and of low quality.…”
Section: Suvmaxmentioning
confidence: 99%
“…However, patients homozygous for the GG variant (rs1799977) of the MLH1 gene (about 8% of patients) do not benefit from the addition of doxorubicin to the treatment 36 . Conversely, patients with aggressive histological (grade 3a FL) and metabolic features (high standardized uptake value on positron‐emitting tomography) could potentially benefit more from anthracycline‐based regimens 42,43 (Table 2) although data supporting this idea are indirect and of low quality.…”
Section: Predictive Biomarkers In Follicular Lymphomamentioning
confidence: 99%
“…[6][7][8][9] Another multicenter retrospective analysis evaluated outcomes of a large cohort of patients with grade 1 to 3A FL treated with front-line bendamustine plus rituximab and found that patients with 3A disease have inferior overall survival and significantly increased risk of disease progression as compared with those with LG disease, which differs from the published experience with R-CHOP. 10 Thus, there is no consensus to guide management of 3A FL. It is clear that grading of FL plays an important role in therapeutic decision-making.…”
Section: Introductionmentioning
confidence: 99%